3(x+2)=2(2+x)

Simple and best practice solution for 3(x+2)=2(2+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=2(2+x) equation:


3(x+2)=2(2+x)

We simplify the equation to the form, which is simple to understand
3(x+2)=2(2+x)

Reorder the terms in parentheses
+(+3x+6)=2*(2+x)

Remove unnecessary parentheses
+3x+6=+2+*(+2+x+)

Reorder the terms in parentheses
+3x+6=+(+4+2x)

Remove unnecessary parentheses
+3x+6=+4+2x

We move all terms containing x to the left and all other terms to the right.
+3x-2x=+4-6

We simplify left and right side of the equation.
+1x=-2

We divide both sides of the equation by 1 to get x.
x=-2

See similar equations:

| 2(-6-5x)=68 | | 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) | | (X+41)+x+78=95 | | 7+2[m-4]=3 | | 90=(3x+13)(5x-7) | | 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 | | 3h+2h+9=54 | | 13=5x+1-3x | | .20*5000= | | 2975+X(175.75)=5962.72 | | 9+-5x=12+-1(6x+7) | | 0.3(4x-2)=-0.8x+9.4 | | 2c^2+9c+10=0 | | 6000-1240= | | (X+41)+95=x+78 | | 2x+9-x=9+2x-6 | | 74=8(c+4)-4 | | 4760/45= |

Equations solver categories